Lussazioni traumatiche acute di rotula - Lup, D.; Ricciarini, M.E.; Summa, P.; Guarracino, R.; Guastafierro, P.; Caldora, P. (Lo Scalpello - Journal, 2018)
ACUTE TRAUMATIC PATELLAR DISLOCATIONAcute patellar dislocation is a common knee injury that occurs most often in adolescents, frequently associated withsport and physical activities. Two-thirds of acute patellar dislocations occur in young active patients less than 20 yearsold. Non-contact knee sprain in flexion and valgus is the leading mechanism for patellar dislocation, accounting for asmany as 93% of all cases. The strong displacement of the patella tears the medial stabilizing structures, and mostly themedial patellofemoral ligament (MPFL), which is almost always injured in acute patellar dislocation, most frequentlyat its femoral attachment. Plain X-ray and CT are mandatory to diagnose bony risk factors for patellar dislocationand plan correction. MRI gives the best information on cartilage and capsulo-ligamentous status for treatmentplanning: free bodies or osteochondral fracture should be treated surgically. Acute patellar dislocation is associatedwith a high rate of recurrent patellar instability, instability symptoms and, eventually, patellofemoral osteoarthritis.A consensus on its management is still lacking. Though most authors have reported good results with conservativetreatment, a surgical approach would be necessary in the presence of severe cartilage damage or a relevant disruptionof the medial stabilizers with instability and subluxation of the patella.